2019
DOI: 10.1016/j.fishres.2018.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of the blue shark (Prionace glauca) in the Indian Ocean

Abstract: Obrigada ao Dr. Rui Coelho por ter aceite orientar este trabalho e por toda a ajuda imprescindível, assim como ao Dr. Karim Erzini. À Daniela Rosa, obrigada por toda a ajuda e pela paciência durante estes meses de trabalho, e também ao Rubén Muñoz-Lechuga pela sua disponibilidade. Obrigada aos observadores do IPMA, Carlos Barbosa e Sérgio Goes, que recolheram as amostras sem as quais esta tese não seria possível, e também à restante equipa do IPMA por me terem feito sentir integrada. Aos meus pais e à minha ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
0
14
1
Order By: Relevance
“…Age and growth studies for most shark species have used the three-parameter VBGF (3-VBGF) to describe growth (Jolly et al, 2013;Drew et al, 2015;Lessa et al, 2015;Baje et al, 2018;Liu et al, 2018;Andrade et al, 2019). In this study, the 3-VBGF, as well as the other three models, presented good fit to the observed length-at-age data for P. kamoharai since their AICc values were <2 showing all models had great support (Burnham and Anderson, 2002).…”
Section: Comparison Of Growth Modelsmentioning
confidence: 67%
See 3 more Smart Citations
“…Age and growth studies for most shark species have used the three-parameter VBGF (3-VBGF) to describe growth (Jolly et al, 2013;Drew et al, 2015;Lessa et al, 2015;Baje et al, 2018;Liu et al, 2018;Andrade et al, 2019). In this study, the 3-VBGF, as well as the other three models, presented good fit to the observed length-at-age data for P. kamoharai since their AICc values were <2 showing all models had great support (Burnham and Anderson, 2002).…”
Section: Comparison Of Growth Modelsmentioning
confidence: 67%
“…The X-ray radiography approach on whole and coronally sectioned centra for P. kamoharai failed to present clear growth bands in this study. Sectioned vertebral centra embedded in resin are the most widely used technique to age sharks (Matta et al, 2017;Andrade et al, 2019). Lessa et al (2015) used sectioned vertebral centra on P. kamoharai specimens captured in the south-western Atlantic and obtained positive results, so its failure in the present study may be because of improper handling or processing of samples.…”
Section: Age and Growthmentioning
confidence: 95%
See 2 more Smart Citations
“…Additionally, Harry (2018) alerts to the fact that many validation studies have reported underestimation in shark and ray ageing studies, especially in the larger and presumably older sharks. Ages can be underestimated if vertebrae cease to grow as maximum size is approached (Andrade et al ., 2019), therefore estimated maximum ages in this study should be considered as low estimates of maximum age for this species. Age validation through a species' lifespan is of extreme importance, as incorrect age and growth parameters will influence longevity, mortality estimates and other biological processes, which are important input parameters for stock assessments and fisheries management (Goldman et al ., 2012; Cailliet, 2015).…”
Section: Discussionmentioning
confidence: 81%